Apatia popular no pensamento político e social brasileiro : uma análise a partir das obras de Oliveira Viana, Caio Prado Júnior e Fernando Henrique Cardoso - Rodrigo Badaró de Carvalho (2022)
The present work is an investigation of the ways in which different intellectual traditions interpreted the Brazilian people throughout the 20th Century. The category of intellectual traditions was chosen to be used as the methodology, understanding that this is the most appropriate method to think about the continuity of certain ideas over time. More specifically, three authors were chosen to be investigated in depth. The works of the conservative Oliveira Viana, the socialist Caio Prado Júnior and the liberal Fernando Henrique Cardoso are the ones being analyzed. Based on the analysis of these important authors of Brazilian Political and Social Thinking and recognizing their internal differences, there’s evidence of the persistence of the diagnosis of a popular incapacity for civic life. In addition to this convergence, there’s also analyses of the impacts of these understandings for the elaboration of these intellectuals' political projects. Finally, the weight of structural racism in the set of interpretations is put into discussion. Through the dialogue with contemporary Brazilian historiography, this work aims to bring elements to suggest a new reading that recognizes the agency of the Brazilian people throughout History. In general terms, it indicates the centrality of the political actions of the subaltern groups in various political and social processes. Lastly, there is a reflection on how these groups constituted forms of resistance and reinvention of life that were not properly observed by important Brazilian intellectuals.